Genomic alterations of the JAK2 and PDL loci occur in a broad spectrum of lymphoid malignancies. Issue 5 (6th February 2016) - Van Roosbroeck, Katrien; Ferreiro, Julio Finalet; Tousseyn, Thomas; van der Krogt, Jo‐Anne; Michaux, Lucienne; Pienkowska‐Grela, Barbara; Theate, Ivan; De Paepe, Pascale; Dierickx, Daan; Doyen, Chantal; Put, Natalie; Cools, Jan; et al.
Abstract : The recurrent 9p24.1 aberrations in lymphoid malignancies potentially involving four cancer‐related and druggable genes ( JAK2, CD274/PDL1, PDCD1LG2/PDL2, and KDM4C/JMJD2Cl ) are incompletely characterized. To gain more insight into the anatomy of these abnormalities, at first we studied 9p24.1 alterations in 18 leukemia/lymphoma cases using cytogenetic and molecular techniques. The aberrations comprised structural (nine cases) and numerical (nine cases) alterations. The former lesions were heterogeneous but shared a common breakpoint region of 200 kb downstream of JAK2 . The rearrangements predominantly targeted the PDL locus. We have identified five potential partner genes of PDL1/2 : PHACTR4 (1p34), N4BP2 (4p14), EEF1A1 (6q13), JAK2 (9p24.1), and IGL (22q11). Interestingly, the cryptic JAK2‐PDL1 rearrangement was generated by a microdeletion spanning the 3′ JAK2 −5′ PDL1 region. JAK2 was additionally involved in a cytogenetically cryptic IGH ‐mediated t (9;14)(p24.1;q32) found in two patients. This rare but likely underestimated rearrangement highlights the essential role of JAK2 in B‐cell neoplasms. Cases with amplification of 9p24.1 were diagnosed as primary mediastinal B‐cell lymphoma (five cases) and T‐cell lymphoma (four cases). The smallest amplified 9p24.1 region was restricted to the JAK2‐PDL1/2‐RANBP6 interval. In the next step, we screened 200 cases of classical Hodgkin lymphoma by interphase FISH and identified PDL1/2 rearrangement ( CIITA ‐ and IGH ‐negative) in four cases (2%), what is a novel finding. Forty (25%) cases revealed high level amplification of 9p24.1, including four cases with a selective amplification of PDL1/2 . Altogether, the majority of 9p24.1 rearrangements occurring in lymphoid malignancies seem to target the programmed death‐1 ligands, what potentiates the therapeutic activity of PD‐1 blockade in these tumors. © 2016 Wiley Periodicals, Inc.